2021
DOI: 10.3920/wmj2020.2587
|View full text |Cite
|
Sign up to set email alerts
|

Determination of patulin and hydroxymethylfurfural in beverages by UPLC-PDA

Abstract: The present study describes using molecularly imprinted polymer (MIP) technology for determination of patulin (PAT) and 5-hydroxymethylfurfural (5-HMF) in beverages by ultra-high performance liquid chromatography coupled to photodiode array (UPLC-PDA). PAT (4-hydroxy-4H-furo[3,2-c]pyran-2(6H)-one) is a mycotoxin produced by Penicillium fungi and Penicillium expansum is probably the most commonly encountered species that infects apples during their growth, harvest, storage or processing. The occurrence of PAT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Mould is a major problem for apples and apple products, including cider. This mould generally affects damaged or fallen apples but could infect apples also during storage or processing [74]. Apples and apple products are the main sources of patulin in the human diet [75].…”
Section: Apple's Microbiota and Pre-fermentative Treatmentsmentioning
confidence: 99%
“…Mould is a major problem for apples and apple products, including cider. This mould generally affects damaged or fallen apples but could infect apples also during storage or processing [74]. Apples and apple products are the main sources of patulin in the human diet [75].…”
Section: Apple's Microbiota and Pre-fermentative Treatmentsmentioning
confidence: 99%
“…The LOD and LOQ documented in the current study were relatively high compared to earlier studies [ 25 , 26 ]. Pernica et al [ 27 ] have reported the levels of LOD and LOQ of 4.9 and 6.6 μg/L of patulin. The values of LOD from 2.6 to 7.5 μg/kg and LOQ of 8.0–15.0 μg/kg were documented in dried fruits, juices, and jams samples [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study thus concluded that molecularly imprinted SPE could be used as an alternative sample preparation method for detecting OTA in pig products. Pernica et al (2021) assessed the effectiveness of using UHPLC-photodiode array detection (PDA) in determining the presence of PAT and potentially hazardous products formed during processing (5-hydroxymethylfurfural) in beverages. The methodology utilised MIP extraction, with separation of PAT from 5-hydroxymethylfurfural within two minutes using a Luna Omega C 18 column while the wavelength of the PDA detector was set at 276 nm.…”
Section: Chromatography With Non-ms Detectionmentioning
confidence: 99%